Adoption of Information Systems and Digital Promotion Strategies Among Rural MSMEs - Fera Widyanata; Dolly Tanzil; Muhammad Bahrul Ulum; Ahmad Khoirun Najib (Jurdimas (Jurnal Pengabdian Kepada Masyarakat) Royal, 2026)
Abstract: This community empowerment initiative aims to enhance the digital readiness of Micro, Small, and Medium Enterprises (MSMEs) in Permata Baru Village, Ogan Ilir Regency, through the implementation of information systems and digital promotion strategies. Prior to the program, local MSME actors faced several challenges, including limited digital literacy, a lack of understanding of online marketing strategies, and minimal utilization of social media as a promotional tool, resulting in restricted market reach. The program adopts an educational and participatory approach, combining community-based learning, interactive discussions, and consultation sessions facilitated by lecturers and students from the Faculty of Economics, Sriwijaya University. The findings indicate strong enthusiasm among MSME participants and an improved understanding of how digitalization can expand market access. Participants have begun to utilize social media platforms such as Instagram, Facebook, and TikTok to promote their products. Overall, this initiative contributes to advancing digital literacy and technology-based marketing skills among rural MSMEs, thereby fostering inclusive and sustainable local economic growth. Keywords: community engagement; digital literacy; digital promotion; information systems; MSMEs; rural development Abstrak: Inisiatif pemberdayaan masyarakat ini bertujuan untuk meningkatkan kesiapan digital Usaha Mikro, Kecil, dan Menengah (UMKM) di Desa Permata Baru, Kabupaten Ogan Ilir, melalui penerapan sistem informasi dan strategi promosi digital. Sebelum program ini dilaksanakan, para pelaku UMKM masih menghadapi sejumlah kendala, seperti terbatasnya literasi digital, kurangnya pemahaman mengenai strategi pemasaran daring, serta minimnya pemanfaatan media sosial sebagai sarana promosi sehingga jangkauan pasar mereka relatif sempit. Program ini mengadopsi pendekatan edukatif dan partisipatif, yang menggabungkan pembelajaran komunitas, diskusi interaktif, dan sesi konsultasi yang dilakukan oleh dosen dan mahasiswa dari Fakultas Ekonomi, Universitas Sriwijaya. Temuan menunjukkan bahwa peserta UMKM menunjukkan antusiasme yang tinggi dan peningkatan pemahaman tentang bagaimana digitalisasi dapat memperluas akses pasar. Mereka telah mulai memanfaatkan platform media sosial seperti Instagram, Facebook, dan TikTok untuk promosi produk. Secara keseluruhan, inisiatif ini berkontribusi untuk memajukan literasi digital dan keterampilan pemasaran berbasis teknologi di kalangan UMKM pedesaan, yang mendorong pertumbuhan ekonomi lokal yang inklusif dan berkelanjutan. Kata kunci: pengabdian kepada masyarakat; literasi digital; promosi digital; sistem informasi; UMKM; pembangunan perdesaan